Interpretasi Hermeneutika-Filosofis: Pralaya dalam Perspektif Kitab Mānava Dharmaśāstra Komparasinya dengan Konsep Kiamat dalam Surah al-Wāqi’ah (Studi Agama Hindu dan Islam) - Adnyana, Ida Bagus Putu (Institut Agama Hindu Negeri Gde Pudja Mataram, 2025)
Abstract The End of Days, commonly known as apocalypse, is a topic widely discussed in every religion. On a large scale involving the universe, it's called cosmic destruction, but on a small scale, like an individual's death, it's referred to as microcosmic destruction. In the Hindu perspective, destruction is seen as pralaya, a condition where everything created returns to merge with its creator. Meanwhile, in the Islamic view, it is called apocalypse (al-Qiyamah or al-Qari’ah). This study aims to compare the concepts of pralaya and kiamat in the Mānava Dharmaśāstra and Surah al-Wāqi’ah. The research uses a descriptive qualitative method with a literature study and a philosophical-hermeneutic approach. This study aims to provide a comprehensive understanding of both concepts. During the research process, three research questions were formulated concerning the interpretation of pralaya in the Mānava Dharmaśāstra, pralaya as a cosmic turning point rather than a final cosmic end, and a comparison of pralaya in the Mānava Dharmaśāstra with kiamat in Surah al-Wāqi’ah. In general, the results show a fundamental similarity: both pralaya and kiamat are depicted as inevitable events that are certain to occur. However, significant differences were found in the purpose, consequences, and narrative focus of these two events. In pralaya, an individual returns to a state of non-activity, ending suffering and the cycle of rebirth without a clear separation between good and evil. Meanwhile, kiamat explicitly divides humanity into two groups: one that will receive rewards in heaven and another that will be punished in hell. The narrative focus of the Mānava Dharmaśāstra is more metaphysical and spiritual, emphasizing the process of returning to the origin, while the narrative of al-Wāqi’ah is more oriented towards moral justice, focusing on rewards and punishments. Keyword: Philosophical-Hermeneutics; Pralaya; Apocalypse; Comparison